Diseño de un prototipo de una máquina tipo industrial para evaluación de fuerzas de tracción-compresión - Hurtado Rincon, Cristhian Camilo; Aguirre Chaparro, César Javier (Universidad Antonio Nariño, 2021)
This project will implement a prototype that evaluates tensile andcompression forces, based on the model of an industrial prototype of a backhoe. The design and simulation of the prototype include: an arm with two pneumatic pistons to change its vertical position, a movement transmission system by means of V-belts, together with an axial type ball bearing, which was selected with the purpose of supporting axial loads of 4.9N and a mass of 500 grams; together with a radial ball bearing that supports radial loads of 2.3N and therefore a mass of 230 grams, which allow changes in horizontal positioning of 180°. The arms have shirts to slide them on and to be able to carry out the respective measurements on the supports of the structure. The proposed design and simulation serves as a basis for analyzing the different stresses and deformations generated on the detected structure in Teflon and PET plastic, varying the vertical rotation angles of the arms for a load of 500 grams, where As a parameter, do not exceed the admissible stress of the Teflon to avoid buckling and therefore the deformation of the structure. The objective of the project is to promote in the student the ability to consolidate theoretical - practical knowledge by approaching a real environment, where we can apply strategies for solving problems based on knowledge of disciplinary areas such as resistance of materials, mechanical design, statics and mechanisms.